Potential Candidates against Staphylococcus aureus and Methicillin-resistant Staphylococcus aureus through the Inhibition of Penicillin-binding Proteins - Nguyen, Tan Khanh; Bich, Van Ngo Thai; Tran, Linh Thuy Thi; Nguyen, Sa Vo Duong; Tran, Manh Hung; Pham, Phu Tran Vinh (Research Perspectives of Microbiology and Biotechnology Vol. 5, 2024)
The increase of multidrug-resistant bacteria, Staphylococcus aureus (SA) and methicillin-resistant Staphylococcus aureus (MRSA) is an alarming problem for global health in recent years and in the near future. To solve this problem, finding new antibiotics is one of the top priorities. In the structure of MRSA bacteria, penicillin-binding proteins (PBPs) play a role in the integrity of the bacterial cell wall and prevent the entry of harmful molecules into the bacteria. Hence, PBPs are the key factors in the mechanism of antibiotic resistance activity of MRSA. Developing therapies for MRSA-associated infections through compounds that directly act on PBPs is a recent promising approach. To achieve this goal, researchers are going to combine in silico, in vitro, and in vivo experiments to screen and elucidate the mechanism by which natural compounds from herbal plants or compounds in compound libraries such as alkaloids and flavonoids, promising antibiotics agents to inhibit MRSA, target PBPs. This review will introduce the structure properties and pathogen characteristics of SA and MRSA and some promising candidates from herbal medicine and commercial compounds with potential antimicrobial properties against SA and MRSA through interaction with housekeeping genes of PBPs. The information from this study will provide important scientific evidence in the evolution of S. aureus to become MRSA and the potential inhibitors against MRSA, which are innovative approaches to combat antibiotic-resistant Staphylococci in the future.